PELATIHAN PENGOLAHAN KOLEKSI DALAM MENDUKUNG PENGEMBANGAN PERPUSTAKAAN DESA - Tjahjanulin Domai; Niken Lastiti V.A.; Anita Tri Widiyawati; Aulia Puspaning Galih (JPM PAMBUDI, 2018)
Community empowerment through the Village Library is a very important tool in increasing the information literacy of rural communities. In the management of the library, the collection is the main thing and human resources are very important in maintaining the existence of the library itself. Subdistrict Junrejo not yet has people who are able to give responsibility for developing and managing the village. Related to these things this dedication to providing training and assistance in processing library collection. The output targets of this devotion are: a) to enrich and add to the repertoire of concepts and theories about the processing of printed and non-printed materials; 2) developing models and strategies on collection management in the development of a village library; c) subdistrict officials and village offices have knowledge of development and have the ability to carry out library material processing activities; and d) communities with sub-districts that can be used to develop education, reading interest, and information literacy. Training in this task is the employees of village and sub-district offices and kindergarten teachers in Junrejo Subdistrict. The implementation method used is theory and practice. Based on the realization and problem solving that has been implemented shows that the overall activity of this devotion has been run in accordance with the objectives, targets, and benefits that have been planned. So that the employees of the sub-district office, village office, and kindergarten teachers in Junrejo Subdistrict, Batu City get provisions to apply knowledge about community empowerment through village libraries and village library management.